Estimation of external disturbance torques on CubeSats to enhance full state attitude estimation accuracy and mission success - Habila, Asia Saeed Kajo (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.